Eu3+‐Activated Borogermanate Scintillating Glass with a High Gd2O3 Content. Issue 5 (28th February 2013) - Sun, Xin‐Yuan; Jiang, Da‐Guo; Chen, Shi‐Wei; Zheng, Guo‐Tai; Huang, Shi‐Ming; Gu, Mu; Zhang, Zhi‐Jun; Zhao, Jing‐Tai; Ballato, J.
<x xml:space="preserve">Abstract</x> Eu3+‐activated borogermanate scintillating glasses with compositions of 25B2O3–40GeO2–25Gd2O3–(10−x)La2O3–xEu2O3 were prepared by melt‐quenching method. Their optical properties were studied by transmittance, photoluminescence, Fourier transform infrared (FTIR), Raman and X‐ray excited luminescence (XEL) spectra in detail. The results suggest that the role of Gd2O3 is of significance for designing dense glass. Furthermore, energy‐transfer efficiency from Gd3+ to Eu3+ ions can be near 100% when the content of Eu2O3 exceeds x = 4, the corresponding critical distance for Gd3+–Eu3+ ion pairs is estimated to be 4.57 Å. The strongest emission intensities of Eu3+ ions under both 276 and 394 nm excitation are simultaneously at the content of 8 mol% Eu2O3. The degree of Eu–O covalency and the local environment of Eu3+ ions are evaluated by the value of Ωt parameters from Judd–Ofelt analysis. The calculated results imply that the covalency of Eu–O bond increases with the increasing concentration of Eu3+ ions in the investigated borogermanate glass. As a potential scintillating application, the strongest XEL intensity under X‐ray excitation is found to be in the case of 6 mol% Eu2O3, which is slightly different from the photoluminescence results. The possible reason may be attributed to the discrepancy of the excitation mechanism between the ultraviolet and X‐ray energy.